Pretending to Be Better Than They Are? Emotional Manipulation in Imprisoned Fraudsters - Wang, Qianglong; Liu, Zhenbiao; Bernat, Edward M.; Vivino, Anthony A.; Liang, Zilu; Bai, Shuliang; Liu, Chao; Yang, Bo; Zhang, Zhuo (Frontiers in Psychology, 2021)
Fraud can cause severe financial losses and affect the physical and mental health of victims. This study aimed to explore the manipulative characteristics of fraudsters and their relationship with other psychological variables. Thirty-four fraudsters were selected from a medium-security prison in China, and thirty-one healthy participants were recruited online. Both groups completed an emotional face-recognition task and self-report measures assaying emotional manipulation, psychopathy, emotion recognition, and empathy. Results showed that imprisoned fraudsters had higher accuracy in identifying fear and surprise faces but lower accuracy in identifying happiness than controls (t=5.26, p<.001; t=2.38, p<.05; t=3.75, p<.001). Significantly lower scores on non-prosocial factors on the Managing the Emotions of Others scale (MEOS) were found for imprisoned fraudsters, relative to controls (t=3.21, p<.01). Imprisoned fraudsters had low scores in the assessment of psychopathy than the control group, especially Factor 1 (t=2.04, p=.05). For empathy, imprisoned fraudsters had significantly higher scores in perspective-taking than controls (t=2.03, p=.05). Correlation analyses revealed that psychopathic traits were positively correlated with non-prosocial factors in both groups. However, the relationships between emotional manipulation and emotional recognition and empathy were not consistent across the groups. The results suggested that the fraudster was like a healthy person, who had lower antisocial tendencies, normal empathy ability, and would like to manipulate others' emotions positively during social interaction.